ALISHER NAVOIYNING “NASOYIM UL-MUHABBAT” TAZKIRASI VA SULAMIYNING “TABAQOT US-SUFIYA” ASARLARI O‘RTASIDAGI MUSHTARAKLIKLAR - Saydullayeva, Dilrabo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
This article analyzes the similarities between Alisher Navoi’s “Nasoyim ul-muhabbat” and Abu Abdurahman Sulami’s “Tabaqat al-sufiyya”. The study focuses on the classification of Sufis, their lives, activities, and spiritual views as described in both works. The findings reveal the interconnection between the two remembrances and their significance in the history of Sufism.